The Impact of Economic Literacy and Environmental Literacy on Student Green Consumer Behavior - Rani Tania Pratiwi; Atin Nuryatin; Wirasmo Prawirasuyasa; Yeyen Suryani; Deden Agustira (International Journal of Educational Management and Innovation, 2023)
One of the reasons for the low quality of the environment today is the activities carried out by humans as consumers. Consumers' positive attitudes towards environmental issues can be encouraged by economic literacy and ecological literacy, which reflect the relationship between the economy and ecology. A person's lack of insight into the environment causes various environmental problems to continue without the perpetrators of destruction realizing it. Solutions to various environmental issues must come from all scientific disciplines, especially the most basic ones in education. Environmentally friendly consumer behavior is individual behavior that is influenced by concern for the environment. This research aims to describe the influence of economic literacy and environmental literacy on environmentally friendly consumer behavior, financial literacy on ecologically friendly consumer behavior, and environmental literacy on social consumer behavior. Environment. Environment. This research was conducted using a quantitative approach and correlational descriptive analysis techniques. This research analyzes the influence of Economic Literacy and Environmental Literacy on Green Consumer Behavior. The research population was students of the Economic Education Study Program, Faculty of Teacher Training and Education, Kuningan University. Data analysis uses multiple regression. The research results show that economic and environmental literacy positively affect environmentally friendly consumer behavior. The findings of this research have implications for efforts to increase consumption of green consumer behavior, which is predominantly triggered by digital media and educational institutions. In addition, the research results show that although environmental literacy positively affects environmentally friendly consumer behavior, the effect is low. This can be improved with a learning approach that seeks to increase student involvement by using the environment as a learning resource. So, the author recommends that for further research, an approach can be used that involves students in utilizing the environment through learning activities that will attract students' interest in studying things related to life and beneficial to the environment.